FEED-FORWARD CONTROL DESIGN FOR ROLL/YAW ATTITUDE FLEXIBLE SPACECRAFT BASED ON THE DISTURBANCE OBSERVER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper addresses the attitude control problem for the coupled roll/yaw dynamics of a flexible satellite in the presence of disturbances from flexible vibrations, unknown dynamics, and external environmental disturbances. To estimate the influence of the vibration torque generated by the flexible appendage, a disturbance observer is introduced to improve the attitude control performance and ensure the robustness as well as the stability of the proposed control. Then, the attitude controller is designed to stabilize and attenuate the estimation error of disturbances. To guarantee the stability of the closed-loop system, a stability analysis of the coupled roll/yaw dynamics of a flexible satellite in the closed-loop system is provided using the Lyapunov method, whereas the gains of the composite controller are designed based on the linear matrix inequality (LMI) approach. Finally, the simulation results of the geostationary-earth-orbit flexible satellite are presented to validate the attitude stabilization performance of the proposed approach.
Keywords: Flexible spacecraft; Attitude stabilisation; Composite control; Linear matrix inequalities